Resilience and occupational well-being of secondary education teachers in Greece - Brouskeli, Vasiliki; Kaltsi, Vasiliki; Loumakou, Maria (Issues in educational research, 2018)
We investigated Greek secondary teachers' resilience and occupational well-being. We aimed to detect the role of participants' demographic characteristics and schools' characteristics, as well as the relationship of teachers' resilience with their occupational well-being. Two hundred and one secondary teachers from fifteen secondary schools participated. Resilience Scale (Wagnild & Young, 1993) was used to measure the teachers' resilience and their occupational well-being was measured by the relative scale of Saaranen, Tossavainen, Turunen, Kiviniemi and Vertio (2007). Results revealed that the urbanisation level of the school seemed to affect resilience as well as occupational well-being. Teachers' scientific specialisation seemed to be related to their resilience levels. Furthermore, teachers' resilience correlates positively with their occupational wellbeing. Apparently, research on teachers' resilience and occupational well-being may be fruitful and enrich their future preparation with educational and consultative interventions that could be beneficial for the educator, the organisation, and the students' progress.